Critical Alliances Economics and Feminism in English Women's Writing, 1880-1914 - Cameron, S. Brooke (University of Toronto Press, 2020)
Critical Alliances argues that late-Victorian and modernist feminist authors saw in literary representations of female collaboration an opportunity to produce new gender and economic roles for women. It is not often that one thinks of female allegiances - such as kinship networks, cultural inheritance, or lesbian marriage - as influencing the marketplace; nor does one often think of economic models when theorizing feminist cooperation. S. Brooke Cameron suggest that, through their representations of female partnership, feminist authors such as Virginia Woolf, Olive Schreiner, George Egerton, Amy Levy, and Michael Field redefined the gendered marketplace and, with it, women's professional opportunities. Interdisciplinary at its core and using a contextual approach, Critical Alliances selects cultural texts and theories relevant to each writer's particular intervention in the marketplace. Chapters look at how different forms of feminist collaboration enabled women to stake their claim to one of the many, emergent professions at the turn of the century.
Description based on print version record.
KU Select 2019: HSS Frontlist Books
Keywords: Literary Criticism / European / English, Irish, Scottish, Welsh; Literature -- History and criticism; Electronic books